Efficient one-pot lactic acid production from cellulose via a Trichoderma reesei and Bacillus coagulans cooperation leveraging substrate-induced secretomes - Shuai Liang; Chang Yu; Jiaming Fu; Yuanming Tao; Zhaojuan Zheng; Jia Ouyang (Bioresource Technology, 2026)

Longitudinal association between metal mixture exposure and non-alcoholic fatty liver disease: A prospective cohort study based on generative adversarial networks - Jiaming Fu; Jinhao Jia; Honghui Li; Guojie Qiao; Zeyang Bai; Limeng Xiong; Yuhan Zhang; Xiaozhe Geng; Hongju Duan; Yuxi Wang; Chunqing Gao; Xiaoyu Li; et al. (Environmental Pollution, 2026)

Coordinated nitrogen placement and rate optimization strengthen root–nitrogen coupling and improve nitrogen use efficiency in dryland maize - Fu Liu; Xiaoyu Ning; Jiaming Yang; Zijun Han; Yunfei Ren; Jinxia Wang; Haibo Hu; Yi Zhou; Xiaogang Yin; Shikun Sun; Juan Han; Yuncheng Liao; et al. (Soil and Tillage Research, 2026)

Unraveling the adverse outcome pathways of metabolic dysfunction-associated steatotic liver disease triggered by environmental mixtures via biological knowledge-driven machine learning - Jiaming Fu; Guojie Qiao; Kerong Ma; Jinhao Jia; Honghui Li; Zeyang Bai; Limeng Xiong; Yuhan Zhang; Xiaozhe Geng; Hongju Duan; Yuxi Wang; Chunqing Gao; et al. (Journal of Hazardous Materials, 2026)

Transport Pathway Evolution and Retention Dynamics of Escherichia Coli in Homogeneous and Heterogeneous Porous Media - Yuanyuan Jia; Zhipeng Tu; Wenjing Zhang; Shutong Jiang; Jiaming Sun; Bo Wan (Transport in Porous Media, 2026)

Investigation of CO2 absorption and desorption performance and mechanism of aqueous [TETAH][Im] in a PTFE hollow fiber membrane contactor - Chunyun Zhou; Yanbin Yun; Chang Li; Jia Liu; Jiaming Mao; Wenjuan Yang; Haiyan Huang; Guoqiang Zhuang; Meng Li (Journal of Environmental Chemical Engineering, 2026)

BnaCIPK9 homoeologs mediate the dosage-dependent regulation of seed oil in allotetraploid Brassica napus L - Nan Wang; Jingquan Tang; Xianfei Hou; Chengtao Quan; Jiaming Mai; Chao He; Rundong Chen; Baolong Tao; yuanguo Gu; Donghai Jia; Tingdong Fu; Jitao Zou; et al. (Theoretical and Applied Genetics, 2026)

Efficacy and Safety of OnabotulinumtoxinA for the Treatment of Masseter Muscle Prominence in a Chinese Population: 6-Month Results From a Phase 3, Randomized, Placebo-Controlled Study - Jiaming Sun; Yuejun Li; Tianjiao Yang; Jia Chang (Toxicon, 2026)

Imidacloprid exposure at population-relevant doses induces hepatic lipid dysregulation: Exploring the role of cGAS-STING pathway-mediated hepatocyte senescence - Yuhan Zhang; Yuqing Dai; Yihong Di; Bing Wu; Xueyan Tian; Limeng Xiong; Zeyang Bai; Jinhao Jia; Jiaming Fu; Xiaoyu Li; Yi Zhao; Hao Hu; et al. (Environmental Research, 2026)

Longitudinal triglyceride-glucose index and Metal Interactions: A multi-model cohort integrating synergistic and antagonistic indices - Jinhao Jia; Yihong Di; Limeng Xiong; Buyun Liu; Zeyang Bai; Jiaming Fu; Yuhan Zhang; Xiaozhe Geng; Yuxi Wang; Chunqing Gao; Guojie Qiao; Hao Hu; et al. (Environmental Pollution, 2026)

Synergistic layer engineering for high-efficiency blue emission in pure-bromide quasi-2D perovskite light-emitting diodes - Jiaming Yu; Bochao Jia; Shuguang Zhang; Yachun Guo; Yue Liang; Jiangshan Chen; Linfeng Lan; Junbiao Peng (Chemical Engineering Journal, 2026)

Imidacloprid induces abnormal glucose metabolism through NF-κB-mediated apoptosis of pancreatic β cells based on population exposure levels - Zhongyuan Zhang; Jiaming Fu; Yihong Di; Honghui Li; Bing Wu; Xueyan Tian; Meiyan Li; Yuqing Dai; Zhuoheng Shen; Jinhao Jia; Zeyang Bai; Limeng Xiong; et al. (Environmental Research, 2025)

Thermostatic nucleic acid amplification technology in foodborne pathogen detection: opportunities and challenges - Moran Zhang; Jiaming Huang; Yongjin Dai; Shanshan Jin; Qianqian Jia; Xiangfei Li; Xinyi Pang; Jing Sun; Yingjian Lu (Critical Reviews in Food Science and Nutrition, 2025)

Gastrodin inhibits hexokinase-2 mediated glycolysis to rescue rotenone-damaged PC12 cells - Min Chen; Jiaming Tian; Buyun Jia; Meng Wang; Anqi Han; Jiming Zhu; Shasha Tian; Xiaoming Gao; Baikun Li; Qinglin Li; Shanshan Li (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

A normalized small waterbody size transition index for remote sensing drought monitoring - Xi Wang; Wen Zhang; Junjie Li; Zhe Wang; Zhen Zhang; Hui Wang; Yanjiao Song; Jiaming Chen; Yi Bao; Bingsun Chen; Qianyu Wang; Jia Chen; et al. (Journal of Hydrology, 2025)

Dynamic response of seabed in wind power of deep-shallow sea induced by internal solitary waves - Jiaming Xiang; Zhuangcai Tian; Youkou Dong; Enjin Zhao; Lei Song; Jianhua Yue; Guoqing Zhou; Xiaolei Liu; Xiujun Guo; Yonggang Jia (Marine Georesources & Geotechnology, 2025)

Enhanced carbon dioxide capture via amphiphobic PVDF membrane modification for membrane contactors: Overcoming wettability challenges - Chang Li; Yanbin Yun; Fengguang Huang; Jiaming Mao; Jia Liu; Wenjuan Yang; Chunyun Zhou; Meng Li (Chemical Engineering Journal, 2025)

Anhydrous deep eutectic solvents-based biphasic absorbents for efficient CO2 capture: Unravelling the critical role of hydrogen bond-mediated electron transfer - Jiaming Mao; Yunqian Ma; Yuhui Ci; Jia Liu; Chang Li; Wenjuan Yang; Chunyun Zhou; Hongwei Xie; Yanbin Yun (Chemical Engineering Journal, 2025)

Analytical Model of Passive Heave Compensator Considering Gas Exchange Between Accumulator and Gas Bottles - Yong Zhan; Mengxuan Hou; Yuzhi Yao; Jiaming Jia; Bailin Yi; Dongyue Qu (Journal of Marine Science and Engineering, 2025)
Dynamic response characteristics of the passive heave compensator with auxiliary gas bottles are investigated in this paper. A mathematical model of the passive heave compensator is developed which includes mechanics, hydraulics and pneumatics. The key innovation of the proposed model is that the thermodynamic model of gas exchange between the piston accumulator and the gas bottles is derived and discussed. Meanwhile, a one-dimensional model of the pipeline resistance effect is established to calculate the pressure drop across the oil pipeline. The proposed model is used to evaluate the different design parameters of the passive heave compensator for heavy lifting cranes. A study was conducted to investigate the influence of the design parameters on the effectiveness of the passive compensator to reduce the payload displacement. The simulation results indicated that substantial improvement may be possible by careful design parameter selection and optimization.

Mechanism of rice bran removal at individual grain and population levels in abrasive rice mill - Ze Sun; Xinlei Wang; Anqi Li; Jiaming Fei; Wenyu Feng; Dan Zhao; Yanlong Han; Fuguo Jia; Hao Li; Shouyu Ji; Zhuozhuang Li (Biosystems Engineering, 2025)

A NH2-UiO-66-TiO2/Al2O3 hollow ceramic membrane with an enhanced photocatalytic oxidation performance of NO - Wenjuan Yang; Wenli Liu; Yuanbo Song; Yangyang Wang; Yanbin Yun; Guicheng Liu; Chang Li; Jiaming Mao; Jia Liu; Meng Li; Chunyun Zhou; Manxiang Wang; et al. (Journal of Environmental Chemical Engineering, 2025)

Investigation of rice debranning mechanism based on tribological behaviour between rice grains - Jiaming Fei; Ze Sun; Dan Zhao; Anqi Li; Fuguo Jia; Yanlong Han; Hao Li; Shouyu Ji; Zhuozhuang Li; Wenyu Feng (Biosystems Engineering, 2024)

Soil infiltration mechanisms under plant root disturbance in arid and semi-arid grasslands and the response of solute transport in rhizosphere soil - Yuanyuan Jia; Huan Huan; Wenjing Zhang; Bo Wan; Jiaming Sun; Zhipeng Tu (Science of The Total Environment, 2024)

Electroactive supramolecular nanoprobes for electrochemical detection of rituximab in non-Hodgkon’s lymphoma patients - Zhiwei Chen; Zheng Zhao; Jiaming Yuan; Qiaoxuan Zhang; Yufeng Wu; Qingjin Wu; Yuheng Liao; Jia-Huan Qu; Ning Gan; Zhengjin Jiang; Qiqin Wang (Chemical Engineering Journal, 2024)

Recent research progress of MOFs-based heterostructures for photocatalytic hydrogen evolution - Jiaming Li; Jia Jia; Deping Wang; Hongjun Dong; Mingshan Zhu (Chemical Engineering Journal, 2024)

Mechanism and toxicity assessment of Cu0/Fe3O4 activated persulfate based on the acceleration cycle of Fe3+/Fe2+ for the degradation of methyl orange - Lanhe Zhang; Qi Zhang; Chuan Xiao; Yanping Jia; Jiaming Wu (Journal of Water Process Engineering, 2024)

DNA Methylation is Involved in Sex Determination in Spinach - Keli Jia; Jiaming Duan; Guangqian Cheng; Heng Li; Shufen Li; Miao Hu (Biochemical Genetics, 2024)

Experimental and theoretical investigation of an ionic liquid-based biphasic solvent for post-combustion CO2 Capture: Breaking through the “Trade-off” effect of viscosity and loading - Jiaming Mao; Yuhui Ci; Jia Liu; Chang Li; Wenjuan Yang; Yanbin Yun; Guicheng Liu; Meng Li; Manxiang Wang (Chemical Engineering Journal, 2024)

Development of a 3D point cloud reconstruction-based apple canopy liquid sedimentation model - Chongchong Chen; Yalan Jia; Jiaming Zhang; Linsen Yang; Yaxiong Wang; Feng Kang (Journal of Cleaner Production, 2024)

Re-N-acetylation of group B Streptococcus type Ia capsular polysaccharide improves the immunogenicity of glycoconjugate vaccines - Jiaming Bei; Jianrong Wu; Jia Liu (Carbohydrate Polymers, 2024)

Biphasic solvents based on dual-functionalized ionic liquid for enhanced post-combustion CO2 capture and corrosion inhibition during the absorption process - Jiaming Mao; Chang Li; Yanbin Yun; Jia Liu; Wenjuan Yang; Meng Li; Lihua Wang; Chunli Li; Wenli Liu (Chemical Engineering Journal, 2024)

Effectively solve the obstacle in the old residential building energy-saving renovation from the perspective of a four-party evolutionary game - Peng Wang; Haiyun Chen; Zhiyuan Si; Ling Jia; Jiaming Wang; Keying Li; Chenglong Wang (Environmental Science and Pollution Research, 2024)

A new strategy for self-bio-driven granular sludge in a continuous-flow reactor: Applying spherical pelletizing granular sludge as a nucleus - Zhuo Sun; Libin Zhang; Xuejiao Huang; Zhongqin Jiang; Jin Wang; Hongxiang Zhu; Jianhua Xiong; Jiaming Zhang; Dandan Jia (Journal of Cleaner Production, 2024)

Non-uniform milling caused by preferential orientation of rice grains in friction rice mills - Jiaming Fei; Wenyu Feng; Shaohang Shen; Yanlong Han; Anqi Li; Xianzhi Hao; Fuguo Jia; Ze Sun; Shouyu Ji; Zhuozhuang Li (Biosystems Engineering, 2023)

Engaging stakeholders in collaborative control of air pollution: A tripartite evolutionary game of enterprises, public and government - Jiaming Wang; Ling Jia; Pan He; Peng Wang; Lei Huang (Journal of Cleaner Production, 2023)

Influence of hemin on structure and emulsifying properties of soybean protein isolate - Jiaming Zhang; Yangyang Jia; Wenjin Wu; Yingying Zhang; Ping Chen; Xiaofang Li; Xuetuan Wei; Chunmei Li; Kaikai Li (Food Chemistry, 2023)

Rapid adaptive evolution of Bacillus coagulans to undetoxified corncob hydrolysates for lactic acid production and new insights into its high phenolic degradation - Jiaming Fu; Zijie Wang; Hongcheng Miao; Chang Yu; Zhaojuan Zheng; Jia Ouyang (Bioresource Technology, 2023)

Numerical investigation of flow similarity of rice grains in friction rice mill and establishment of scale-up rule - Anqi Li; Fuguo Jia; Jiaming Fei; Yanlong Han; Peiyu Chen; Wenyu Feng; Xianzhi Hao; Shaohang Shen; Hao Li (Computers and Electronics in Agriculture, 2023)

Effects of operating conditions on supercritical methanol liquefaction of polypropylene - Binbin Fu; Litao Geng; Guangchao Jia; Zhilong Yuan; Peitao Zhao; Rongyang Zhao; Cuiping Wang; Jiaming Li (Journal of Environmental Chemical Engineering, 2023)

Study on dynamic response mechanism of rice grains in friction rice mill and scale-up approach of parameter based on discrete element method - Anqi Li; Fuguo Jia; Yanlong Han; Peiyu Chen; Yinglong Wang; Jincheng Zhang; Xianzhi Hao; Jiaming Fei; Shaohang Shen; Wenyu Feng (Innovative Food Science & Emerging Technologies, 2023)

The role of the joint capsule in the stability of the elbow joint - Fang Wang; Hao Wang; Mingxin Li; Shuoqi Jia; Jiaming Wang; Jianguo Zhang; Yubo Fan (Medical & Biological Engineering & Computing, 2023)

The mechanism of bran layer removal in friction rice mills - Jiaming Fei; Wenyu Feng; Fuguo Jia; Yanlong Han; Peiyu Chen; Anqi Li; Yinglong Wang; Jincheng Zhang; Shaohang Shen; Xianzhi Hao (Biosystems Engineering, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

Breakage mechanism of brown rice grain during rubber roll hulling - Peiyu Chen; Fuguo Jia; Jincheng Zhang; Yanlong Han; Anqi Li; Yinglong Wang; Jiaming Fei; Shaohang Shen; Wenyu Feng; Xianzhi Hao (Biosystems Engineering, 2023)

Excess pore water pressure and seepage in slopes induced by breaking internal solitary waves - Zhuangcai Tian; Lei Jia; Jiaming Xiang; Guotao Yuan; Kun Yang; Jun Wei; Mingwei Zhang; Honglei Shen; Jianhua Yue (Ocean Engineering, 2023)

Numerical simulation approach for predicting rice milling performance under different convex rib helix angle based on discrete element method - Anqi Li; Fuguo Jia; Shaohang Shen; Yanlong Han; Peiyu Chen; Yinglong Wang; Jincheng Zhang; Wenyu Feng; Jiaming Fei; Xianzhi Hao (Innovative Food Science & Emerging Technologies, 2023)

Hydrogenation of biomass pyrolysis oil using enhanced reduction catalytic capacity cellular by expressing excavated carbonyl reductase - Chongyang Bu; Hui Qiao; Lihua Zou; Yuanming Tao; Jiaming Fu; Chao Liu; Zhaojuan Zheng; Jia Ouyang (Fuel, 2023)

A study on the effects of anion, cation, organic compounds, and pH on the release behaviors of As and Sb from sediments - Haibo Wang; Jiaming Xu; Mario Alberto Gomez; Zhongliang Shi; Yongfeng Jia (Environmental Science and Pollution Research, 2021)